PENERAPAN PERMAINAN KERETA ANGKA UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG ANAK USIA DINI - Triandini, Yuli; Atiyyah, Sa’adatul (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
Numeracy is a basic ability that must be possessed by children. Through arithmetic, children will learn to solve problems (problem solving) accustomed to arithmetic which always happens in every day-to-day activities. But early childhood introducing numbers is not easy, therefore it is needed support as a medium or interesting game for children so that the introduction of numbers and counting becomes easy and fun. The purpose of this study is to implement the number train game to improve the numeracy ability of group B children in Al-Islah Genteng Banyuwangi Kindergarten. The method used is a Hopkins model classroom action research with research subjects 25 children in group B procedures for data collection by observation, and tests. Qualitative and quantitative data analysis techniques. The results showed that there was a significant increase in the ability to count early childhood through the numbers train game.